2020
DOI: 10.1002/dta.2906
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the μ‐opioid receptor by alicyclic fentanyls: Changes from high potency full agonists to low potency partial agonists with increasing alicyclic substructure

Abstract: Fentanyl analogs represent an important group of new psychoactive substances and knowing their efficacy and potency might assist in interpreting observed concentrations. The potency of fentanyl analogs can be estimated from in vitro studies and can be used to establish structure-activity relationships. In this study, recombinant CHO-K1 cells (AequoScreen) expressing the human μ-opioid receptor were used to establish dose-response curves via luminescent analysis for cyclopropyl-, cyclobutyl-, cyclopentyl-, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For reference, the potency of 5i is comparable to morphine with an EC50 of 430 nm. 65 In conclusion, we have demonstrated how simple mono-protected amino acid ligands can be used to protect allylamines from rapid decomposition, which in turn protects the Pd catalyst, thereby allowing a reaction that had previously given trans-addition products through a directed Mizoroki-Heck reaction to become selective for cis-addition through a directed C-H activation pathway. This technology allows for a variety of 2° and 3° allylamine substrates to be derivatised, including carbocyclic alkenes, which were not previously accessible with other processes.…”
Section: Figure 2 Examination Of Mor Activity Of 3-arylallylamines Us...mentioning
confidence: 89%
See 1 more Smart Citation
“…For reference, the potency of 5i is comparable to morphine with an EC50 of 430 nm. 65 In conclusion, we have demonstrated how simple mono-protected amino acid ligands can be used to protect allylamines from rapid decomposition, which in turn protects the Pd catalyst, thereby allowing a reaction that had previously given trans-addition products through a directed Mizoroki-Heck reaction to become selective for cis-addition through a directed C-H activation pathway. This technology allows for a variety of 2° and 3° allylamine substrates to be derivatised, including carbocyclic alkenes, which were not previously accessible with other processes.…”
Section: Figure 2 Examination Of Mor Activity Of 3-arylallylamines Us...mentioning
confidence: 89%
“…Interestingly, this was even lower than the previously reported EC50 for fentanyl determined from mini-Gi and β-arrestin recruitment assays, indicating the suitability of the γ9 assay. 65 For 5i, the γ9 assay provided an EC50 of 505 ± 129 nM (Figure 2c). For reference, the potency of 5i is comparable to morphine with an EC50 of 430 nm.…”
Section: Figure 2 Examination Of Mor Activity Of 3-arylallylamines Us...mentioning
confidence: 97%
“…There is scant information available regarding the in vivo pharmacodynamics of cyclopropylfentanyl (EMCDDA 2018a ). In vitro studies show that cyclopropylfentanyl displays a binding affinity in the low nanomolar, or sub-nanomolar, range for µ-opioid receptors (Baumann et al 2018 ; Eshleman et al 2020 ; Hassanien et al 2020 ; Wilde et al 2019 ; Åstrand et al 2020a ; Åstrand et al 2020b ). A preclinical study from the 1960s compared the antinociceptive effects of various fentanyl analogs and reported that cyclopropylfentanyl exhibits a potency somewhat lower than fentanyl but higher than acetylfentanyl and butyrfentanyl (Janssen and Van der Eycken 1968 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, information about the in vivo biological effects of cyclopropylfentanyl is lacking. In vitro studies show that the drug is a fully efficacious µ-opioid receptor agonist with a receptor binding affinity in the low nanomolar range and potency similar to fentanyl (Eshleman et al 2020;Hassanien et al 2020;Wilde et al 2019;Åstrand et al 2020a;Åstrand et al 2020b). An animal study performed in the 1960s compared the antinociceptive effects of different fentanyl analogs in mice and rats and reported that cyclopropylfentanyl was slightly less potent than fentanyl but more potent than acetylfentanyl, butyrfentanyl, as well as the reference substance pethidine (Janssen and Van der Eycken 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation